Memorias de la Segunda Guerra Mundial en o reino de Gonçalo M. Tavares - Lasci, Maria Laura (Revista de Filología Románica, 2017)
Set during and after the Second World War and also incorporating a description of the Holocaust, the tetralogy O Reino by Portuguese writer Gonçalo M. Tavares uses parody to deal with recognizable sets of discursive traditions, social practices and emblematic figures which make up cultural memories related to the war. Such parody forces readers to go beyond rigorous categorizations and to perceive the heterogeneity of experiences behind memorialization. It ultimately helps to rethink the conceptual basis of both individual and collective memory, namely the notions of subject, object and of society.